Ingeborg Bachmann: Wer spricht? Eine Analyse der Sprache und des Subjekts in dem Erzählband Das dreißigste Jahr (1961) - Egner, Thorsten (German Language and Literature, 2016)
This dissertation analyses the formation, function and portrayal of language and the subject in the narrative cycle The Thirtieth Year (Das dreißigste Jahr) by the Austrian writer Ingeborg Bachmann (1926-1973), in light of the theories brought forward by the poststructural movement. The traditional outlook on the subject is one that regards it as being autonomous. This autonomy is challenged by the narrative cycle: the analysis shows, how subjects are constructed by a web of interconnecting discourses. In fact, the very qualities from which the subject forms its identity are conferred by the other, which forbids any notion of reflecting on the subject in an autonomous manner. The narratives demonstrate, how the subject will always find itself in an indefinite process of becoming, a process which solicits a different approach, i.e. a change of consciousness for its acknowledgement - one which offers the subject a space to probe its own becoming. Subsequently, this different method of acknowledgement is also confined to the given order. The re-imagining, which the different subjects perform throughout the narrative cycle, show, that Bachmann's subjects are neither fully predestined, nor are they fully autonomous. Although agency is outlined by the given order, the subject is still able to re-evaluate its agency in previously unmediated ways. This shows that ways of existing are not as unalterable as suggested by the given structures. By re -assessing all approaches of autonomous agency, this narrative cycle sensitises the reader to structures that form the subject, and possible ways in which it is thereby oppressed. The narratives expose the mechanisms that form socially recognisable subjects and, more importantly, give voice to those subjects, who find themselves on the periphery of the normative majority. To do so, the dissertation employs theories, which have been categorised as 'poststructural.' These theories lend themselves well to disclosing the repressive character of governing norms and to problematize attempts to universalise certain paradigms. For instance, the assumption that language constitutes identity of the subject, amongst other factors, is re-evaluated in the sense that language and discourse, in fact, restrict and limit the subject in its quest for identity. Bachmann's later works (i.e. Malina (1971), Simultan (1970), Der Fall Franza (1978)) have been the subject of poststructural scrutiny, especially from a feminist perspective. The narrative cycle The Thirtieth Year, however, has received little attention by theorists employing poststructural means of analysis. The dissertation therefore sets out to show that valuable insights can be gained when reading the text from a poststructural perspective.